IMPLEMENTASI PENDEKATAN KETELADANAN ORANG TUA UNTUK MENINGKATKAN MORALITAS ANAK USIA DINI - Mufidatul Munawaroh; Mohamad Syaifullah Abid; Winnuly (Universitas Islam Darul Ulum, 2026)
This study aims to conduct an in-depth examination of the implementation of a parental role-modeling approach in enhancing the morality of early childhood (AUD). The background of this study is grounded in the critical importance of parents as primary role models in the process of internalizing moral values in children. This research employs a qualitative method with a case study design, involving five families with children aged 4 to 6 years as research subjects. Data were collected through in-depth interviews, participant observation, and analysis of relevant documents. The findings indicate that parental role-modeling practices, encompassing positive behavior, open communication, and consistency in the application of moral values make a significant contribution to children’s moral development. Children who are exposed to positive role modeling tend to demonstrate characteristics such as empathy, honesty, and responsibility more optimally. Based on these findings, it can be concluded that the implementation of a parental role-modeling approach is an effective strategy for improving early childhood morality, while also reinforcing the importance of parents as constructive behavioral models for their children.